2010
DOI: 10.1002/uog.7744
|View full text |Cite
|
Sign up to set email alerts
|

Ductus venosus velocimetry in monitoring pregnancy in women with pregestational diabetes mellitus

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…The sensitivity of the ductus venosus index in predicting adverse perinatal outcome in pre-existing diabetic pregnancies was thus 53.3% and specificity was 74.5%, with a positive predictive value of 32% and negative predictive value of 87.7%. The authors concluded that it should be useful to include ductus venosus Doppler indices as part of antenatal screening of pregnancies complicated by pre-existing diabetes mellitus (Wong et al, 2010).…”
Section: Ductus Venosus Doppler Waveformsmentioning
confidence: 99%
“…The sensitivity of the ductus venosus index in predicting adverse perinatal outcome in pre-existing diabetic pregnancies was thus 53.3% and specificity was 74.5%, with a positive predictive value of 32% and negative predictive value of 87.7%. The authors concluded that it should be useful to include ductus venosus Doppler indices as part of antenatal screening of pregnancies complicated by pre-existing diabetes mellitus (Wong et al, 2010).…”
Section: Ductus Venosus Doppler Waveformsmentioning
confidence: 99%
“…Umbilical artery (UA) Doppler velocimetry is widely used to monitor high‐risk pregnancies; however, it has not been shown to be an effective test of fetal well‐being in diabetic pregnancies . Similarly, the efficacy of ductus venosus Doppler velocimetry for monitoring fetuses of diabetic pregnancies is unsatisfactory …”
Section: Introductionmentioning
confidence: 99%
“…При СД в ВП выявлены наиболее ранние (до 10-й недели) отклонения ГД от нормы [52]. Однако чувствительность пульсационного индекса вены (ПИВ) в ВП невысокая -53,3%, а специфичность -74,6% [53]. Минутный объем ВП ниже в группе диабета (94,3 мл/мин/кг) по сравнению с таковыми в контроль-ной группе (109,5 мл/мин/кг).…”
unclassified